Multi-Criteria Decision Approach: An Evaluation of Coastal Tourism Vulnerability in the Mandalika, Indonesia - Mugi Rahardjo; Evi Gravitiani; Ika Alicia Sasanti (School of Postgraduate Studies, Diponegoro Univer, 2025)
Climate change has emerged as a global concern in the 21st century, posing a significant threat to ecosystems and human populations. The impact of climate change on coastal tourism sectors is expected to be substantial, particularly given that roughly 50% of global tourism is concentrated in coastal regions. Environmental change presents a fundamental challenge for coastal tourism planners, necessitating the application of a model framework to manage and promote sustainable development in the face of climate change. This study focuses on the application of such a framework in the Mandalika Region of Indonesia, with the primary objective being the assessment of vulnerability, key criteria, and potential solutions for coastal tourism issues in the area. The research draws on both primary sources, such as interviews with expert specialists, and secondary data through a comprehensive literature review. The research methodology utilizes the Analytical Hierarchy Process (AHP) within the context of Multi-Criteria Decision Making (MCDM) software for coastal tourism hazard management, enabling decision-makers to evaluate and prioritize vulnerability and hazard criteria and sub-criteria according to a set of preferences, criteria, and alternatives. The study also outlines a range of policy designs applied in the Mandalika Region to determine key sustainable weights from criteria and sub-criteria, with findings indicating that human activities carry the greatest weight as a criterion influencing tourism vulnerability in the Mandalika Region. The sub-criteria related to road construction are factors that influence tourism vulnerability in the Mandalika coastal area. Furthermore, the alternative that is chosen as a response to vulnerability solutions is persistent adaptation action. Therefore, it is hoped that this research will be able to overcome the problem of vulnerability due to climate change, especially in the tourism sector through the synergy of all actors involved through policy recommendations.